Trio Album for violin, violoncello & piano, vol. III Violoncello part - CUI, Cesar [et.al] (The Boston Music Co.)
BoleronAndante MelodiquenA DoubtnVivacenSerenadenSpanish dancenNarcissiusnStandchennWaltz